AN EMPIRICAL STUDY ON THE INFLUENCE OF CAMPUS LIFE SATISFACTION TOWARDS ACADEMIC ACHIEVEMENT AMONG UNDERGRADUATE STUDENTS - Ezanee Mohamed Elias; Alvin Tan En Zhe; Azman Ta’a; Norlila Mahidin; Santhisegaran Nadarajan, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
These are among the studies that strive to connect the relationship between academic achievement and student life satisfaction in a higher learning institution. This study was conducted using a quantitative method on undergraduate students from three academic colleges at Universiti Utara Malaysia. Three hundred and seventy-nine students took part in the online survey. The data was collected over the course of two months using a Google form. The questionnaires were broken down into three sections: demographic information, factors impacting students' life happiness in relation to academic accomplishment, and overall life satisfaction. A very well-known statistical software was used to analyse the data and perform various analyses such as reliability and consistency between independent variables and dependent variable. The outcomes reveal that the two factors have durable and moderate associations. The university is encouraged to focus on providing a better on-campus life experience for undergraduate students. Other factors that may impact undergraduate students' life satisfaction should be explored in the future.